How much and what kind of vocabulary do marine engineers need for adequate comprehension of ship instruction books and manuals? - Đurović, Zorica; Vuković-Stamatović, Milica; Vukičević, Miroslav (Círculo de Lingüística Aplicada a la Comunicación, 2021)
Considering the importance of adequate understanding of instruction books and manuals on board vessels all over the world, as well as the challenges it imposes to the English language teachers and course designers, this paper aims to answer important research questions in relation to the quantity and type of vocabulary required for their adequate reading comprehension. In this study we use the method of Lexical Frequency Profiling and the software developed by Anthony Laurence – AntWordProfiler 1.4.0w. The corpus is comprised of 1,769,821 running words obtained from instruction books and manuals of various ship and machinery types. The results of this study point to the high technicality and lexical demand of the corpus, which calls for a highly technical English courses’ design and further research in marine engineering (English) vocabulary. Additionally, the research findings point to the need of creating a marine engineering-specific word list.